Crebanine induces ROS-dependent apoptosis in human hepatocellular carcinoma cells via the AKT/FoxO3a signaling pathway - Tan, Jiajie; Xiang, Yuling; Xiong, Yuanguo; Zhang, Yaoyuan; Qiao, Boyang; Zhang, Hong (Frontiers in Pharmacology, 2023)
Background: Hepatocellular carcinoma (HCC), as an aggressive cancer with a high mortality rate, needs high-efficiency and low-toxicity drug therapy. Natural products have great potential as candidate lead compounds for the development of new HCC drugs. Crebanine is an isoquinoline alkaloid derived from Stephania with various potential pharmacological effects such as anti-cancer. However, the molecular mechanism underlying crebanine-induced liver cancer cells apoptosis has not been reported. Here, we investigated the effect of crebanine on HCC and identified a potential mechanism of action. Methods: In this paper, we intend to detect the toxic effects of crebanine on hepatocellular carcinoma HepG2 cells through a series of in vitro experiments, including detecting the effects of crebanine on the proliferation of HepG2 cells using the CCK8 method and plate cloning assay, observing the growth status and morphological changes of crebanine on HepG2 cells by inverted microscopy; and using the Transwell method to determine the the effect of crebanine on the migration and invasion ability of HepG2 cells; using Hoechst 33258 assay to stain cancer cells, thus observing the effect of crebanine on the morphology of HepG2 apoptotic cells, and detecting the apoptotic state and level of HepG2 cells by flow cytometry; using ROS kit and JC-1 assay kit to detect the changes of reactive oxygen species and mitochondrial membrane potential of HepG2 The immunofluorescence assay was taken to verify whether crebanine had an effect on the expression of p-FoxO3a in cancer cells; the Wetern blot assay was also used to examine the effect of crebanine on proteins related to the mitochondrial apoptotic pathway and its effect on the regulation of the relative protein expression of AKT/FoxO3a axis; after this, NAC and AKT inhibitor LY294002 were used to cells were pretreated with NAC and AKT inhibitor LY294002, respectively, in order to further validate the inhibitory effect of crebanine. Results: It was shown that crebanine effectively inhibited the growth and capacity of HepG2 cells migration and invasion in a dose-dependent manner. Furthermore, the effect of crebanine on the morphology of HepG2 cells was observed through microscopy. Meanwhile, crebanine induced apoptosis by causing reactive oxygen species (ROS) burst and mitochondrial membrane potential (MMP) disrupt. We found that crebanine could down-regulate Bcl-2 and up-regulate Bax, cleaved-PARP, cleaved-caspase-3 and cleaved-caspase-9, but these effects were overturned by ROS inhibitor N-acetylcysteine (NAC). Crebanine also down-regulated p-AKT and p-FoxO3a, and the PI3K inhibitor LY294002 significantly enhances this effect. We also found that the expression of AKT/FoxO3a signaling pathway was ROS-dependent. As shown by Western blots, NAC could partially attenuate the inhibitory effect of crebanine on AKT and FoxO3a phosphorylation. Conclusion: Based on our results, our results suggest that crebanine, as a compound with potential anticancer activity, has significant cytotoxic effects on hepatocellular carcinoma,and it likely induces apoptosis via ROS in the mitochondrial pathway and simultaneously affects the biological function of HCC via the ROS-AKT-FoxO3a signaling axis.